(untitled) (Research, Society and Development, 2021)
Introduction: Benzodiazepines are the most used psychotropic drugs globally and have pharmacological properties that provide sedative, hypnotic, anxiolytic, anticonvulsant and muscle relaxant action. The effectiveness of benzodiazepines is well documented in short-term treatments, but long-term use is contraindicated due to the risk of adverse effects, including dependence. Purpose: to demonstrate the long-term effect of benzodiazepine use by the elderly. Methodology: A bibliographic and webliographic review was carried out from July 2020 to August 2021, using the Scientific Electronic Library Online – SciELO, US National Library of Medicine, National Institutes of Health (PubMed), Library databases. Virtual Health (BVS) and Google Scholar. It was also used the consultation of books and periodicals present in the Library of the University Center of Patos de Minas. After applying the inclusion and exclusion criteria, an analysis of 22 publications was performed. Results and Discussion: The study of selected bibliographies showed that the use of benzodiazepines among the elderly has a high prevalence. In addition, this class of drugs is not recommended for use by the oldest old, aggravating its consequences even more when the treatment is carried out in the long term, exacerbating a series of adverse events without being effective in this form of use. Conclusion: it is important to look for less harmful ways to remedy complaints about sleep and anxiety in the oldest old and also to train health professionals in order to identify medications not recommended for the elderly and propose ways to optimize prescriptions.